4D BIM for Construction Logistics Management - Kane Whitlock; Fonbeyin Henry Abanda; Marcelline Blanche Manjia; Chrispin Pettang; George Elambo Nkeng (CivilEng, 2021)
This study presents an investigation into the extent to which emerging building information modelling (BIM) can be applied to construction logistics management (CLM). Given the specialist nature of the domains, the study employed an in-depth qualitative interview, whereby six experts were interrogated about their experiences of BIM for CLM. The study found the main applications of BIM on CLM to be the creation of three-dimensional (3D) site layout plans and four-dimensional (4D) coordination of site processes and common user plant, updating the 4D logistics plan as the project progressed and collaboration in BIM-based logistics coordination. Furthermore, there was a consensus amongst interviewees on improvement in site safety, comprehension of logistics information, efficiency on site, and effectiveness of layout planning as the main benefits. Lastly, the lack of training with implications on understanding was one of the main barriers to applying BIM to CLM. The findings from this study have the potential to stimulate the uptake of BIM by construction logistics practitioners. By so doing, the performance construction project delivery can be improved, and waste can be minimised or eliminated.